Status of Nigerian English - Aseri, Yahia (Universitas Pendidikan Ganesha, 2023)
English emerged in the Nigerian context as a result of the need to communicate with many people from different ethnic backgrounds who speak different languages. However, the uniqueness of Nigerian English appears, which is different from standard English. This study aims to analyze the status of Nigerian English by explaining the morphological and syntactic features and how they differ from Standard English. This study uses a descriptive qualitative approach. The data will be carefully collected to represent various morphological and syntactical aspects. Data will be collected by conducting text analysis and interview, both written and spoken text in Nigerian English. The data collected will be analysed systematically. The result of this study presents the morphological and syntactical features of Nigerian English and how they differ from Standard English. With a brief commentary on its distinct identity, the paper concludes the justification of the notion that Nigerian English must be regarded as one of the world’s Englishes.